الاضطرابات النفسية في زمن الأزمات المركبة: بين الفردانية والتضامن الاجتماعي - غدايفي، هند; الأسود، يوسف (جامعة المنستير - تونس, 2025)
الملخص (باللغة العربية) تشهد المجتمعات المعاصرة ما يمكن تسميته بـ الأزمة المركبة، حيث تتقاطع الأزمات الصحية والبيئية والاقتصادية والجيوسياسية لتنتج هشاشة نفسية واجتماعية غير مسبوقة. لقد أصبح القلق والاكتئاب واضطرابات ما بعد الصدمة ملامح أساسية لعصر الأزمات، مما يطرح أسئلة ملحة حول قدرة النماذج العلاجية الفردية التقليدية على الاستجابة لهذا الواقع. تهدف هذه المداخلة إلى تقديم قراءة نظرية نقدية لعلاقة الأزمات المركبة بالاضطرابات النفسية، من خلال ثلاثة محاور رئيسية: 1. تحليل العلاقة بين الأزمات المعاصرة وارتفاع نسب الاضطرابات النفسية: كيف تؤدي ظروف اللاتيقن، انهيار منظومات العمل، وتراجع دولة الرفاه إلى تفاقم القلق الجماعي والاكتئاب. 2. الثقافات المحلية والحركات الاجتماعية كموارد علاجية بديلة: تجاوز التصورات الكلاسيكية للعلاج النفسي الفردي نحو اعتبار الذاكرة الجماعية، التضامن الاجتماعي، والإبداع الثقافي أدوات علاجية تسهم في ترميم المعنى وإعادة بناء الذات. 3. جدلية الفردانية والتضامن في مواجهة الانهيار: نقد النزعة الفردانية التي تعمق العزلة النفسية، مقابل إبراز دور شبكات الدعم الاجتماعي في تعزيز استراتيجيات الصمود والتحول. ترتكز هذه المداخلة على مقاربة نظرية عابرة للتخصصات، تستند إلى علم النفس النقدي والتحليل الاجتماعي للأزمات، بهدف المساهمة في بلورة تصور بديل للاضطرابات النفسية في زمن التحولات الكبرى. abstract: Contemporary societies are experiencing what can be described as a compound crisis, in which health, environmental, economic, and geopolitical disruptions intersect to produce unprecedented psychological and social fragility. Anxiety, depression, and post-traumatic stress disorders have become defining features of this age of crises, raising urgent questions about the ability of traditional, individually oriented therapeutic models to address this new reality. This paper offers a critical theoretical reading of the relationship between compound crises and psychological disorders through three main axes: 1. Analyzing the link between contemporary crises and the rise in mental disorders: how uncertainty, the collapse of work systems, and the retreat of the welfare state exacerbate collective anxiety and depression. 2. Local cultures and social movements as alternative therapeutic resources: moving beyond classical notions of individual psychotherapy toward recognizing collective memory, social solidarity, and cultural creativity as therapeutic tools that restore meaning and rebuild the self. 3. The dialectic of individualism and solidarity in times of collapse: critiquing the individualistic tendencies that deepen psychological isolation while emphasizing the role of social support networks in fostering resilience and transformation. The paper adopts an interdisciplinary theoretical approach grounded in critical psychology and social analysis of crises, aiming to contribute to a renewed understanding of psychological disorders amid major global transformations.
Interventio,
Keywords: الأزمات المركبة; الاضطرابات النفسية; علم النفس النقدي; التضامن الاجتماعي; العلاج الثقافي; القلق الجماعي; الصمود النفسي; compound crises; psychological disorders; critical psychology; social solidarity; cultural therapy; collective anxiety; psychological resilience.